Mixing and average mixing times for general Markov processes. Issue 3 (14th August 2020) - Anderson, Robert M.; Duanmu, Haosui; Smith, Aaron
Abstract: Yuval Peres and Perla Sousi showed that the mixing times and average mixing times of reversible Markov chains on finite state spaces are equal up to some universal multiplicative constant. We use tools from nonstandard analysis to extend this result to reversible Markov chains on compact state spaces that satisfy the strong Feller property.